2015
DOI: 10.1007/s40520-015-0405-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D is associated with a reduction in upper and lower limb muscle strength and physical performance in post-menopausal women: a retrospective study

Abstract: Our results support the hypothesis that there is a significant positive association among serum 25(OH)D3 levels and upper and lower limb muscle functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Compromised muscle strength and physical performance is a common manifestation of vitamin D deficiency in generally healthy older individuals 45,46. The current study has shown that serum 25(OH)D concentration is a positive predictor of muscle strength (as measured by grip strength) at both the end of winter and the end of summer, and this association was stronger at the end of summer, when vitamin D status was higher.…”
Section: Discussionsupporting
confidence: 48%
“…Compromised muscle strength and physical performance is a common manifestation of vitamin D deficiency in generally healthy older individuals 45,46. The current study has shown that serum 25(OH)D concentration is a positive predictor of muscle strength (as measured by grip strength) at both the end of winter and the end of summer, and this association was stronger at the end of summer, when vitamin D status was higher.…”
Section: Discussionsupporting
confidence: 48%
“…Low levels of vitamin D are associated with a decrease in muscle strength , and vitamin D supplementation has been shown to improve muscle strength and gait, with a reduction in falls . Severe vitamin D deficiency can lead to a reduction in proximal muscle strength and size as well as increased IMNCT .…”
Section: Discussionmentioning
confidence: 99%
“…Increased IMNCT also correlates with a range of measures of neuropathy, including intraepidermal nerve fibre density, suggesting a link with neuropathy rather than its occurrence as a consequence of muscle atrophy. Low levels of vitamin D are associated with a decrease in muscle strength [27], and vitamin D supplementation has been shown to improve muscle strength and gait, with a reduction in falls [28]. Severe vitamin D deficiency can lead to a reduction in proximal muscle strength and size [8] as well as increased IMNCT [7,29].…”
Section: Discussionmentioning
confidence: 99%
“…In observational studies, optimal serum 25(OH)D levels have been significantly associated with improved musculoskeletal function and muscle strength (Bischoff-Ferrari et al, 2004[6]; Visser et al, 2003[36]). Further, postmenopausal women who were vitamin D deficient presented worse upper and lower limb muscle strength and physical performance compared to vitamin D sufficient control group (Iolascon et al, 2015[21]). Skeletal muscle cells have vitamin D receptor and adequate protein synthesis in these cells, which might be directed through vitamin D function (Holick, 2007[20]).…”
Section: Introductionmentioning
confidence: 99%